Proyeksi Kebutuhan dan Perkembangan Satuan Pendidikan di Kabupaten Sorong Tahun 2026 - 2046 - Waode Alma Syafira; La Ibal; Sulkipli Sulkipli (Universitas Muhammadiyah Sorong, 2024)
This study analyzes the projected needs and development of the number of schools in Sorong Regency at the elementary, junior high, and senior high school levels from 2026 to 2046. The study results indicate an increase in the number of educational units across all levels, although growth is uneven across districts. The Aimas and Mariat districts experienced significant increases, while several districts such as Klaso, Saengkeduk, and Botain still have minimal educational facilities. This condition reflects disparities in access between central and peripheral areas. The increase in the number of schools in certain areas needs to be accompanied by improvements in educational quality, infrastructure, and equitable distribution of teaching staff. The results of this study provide a basis for the local government to design inclusive, equitable, and sustainable educational development policies to support the enhancement of human resource quality in Sorong Regency.